Revision of the genus Pelecinobaccha Shannon, description of Relictanum gen. nov., and redescription of Atylobaccha flukiella (Curran, 1941) (Diptera: Syrphidae) - Miranda, Gil Felipe Gonçalves; Marshall, Stephen A.; Skevington, Jeffrey H. (Zootaxa, 2014)
Recent phylogenetic analyses of Ocyptamus Macquart, 1834 (Diptera, Syrphidae) confirmed the paraphyly of this genus and provided evidence to divide it into several monophyletic subgroups, of which the largest is the clade traditionally treated as the Ocyptamus tristis species group. This group is here redefined, divided into the genera Pelecinobaccha Shannon, 1927 and Relictanum gen. nov., and revised along with the closely related and newly resurrected genus Atylobaccha Hull, 1949. Twenty-four new species (22 in Pelecinobaccha and two in Relictanum) are described and 35 species (27 in Pelecinobaccha, seven in Relictanum and Atylobaccha flukiella Curran, 1941) are redescribed. Pelecinobaccha is divided into four species groups (P. adspersa species group, P. brevipennis species group, P. peruviana species group and P. susio species group). An identification key, illustrations and distribution maps for all species from this study are also presented.